2017
DOI: 10.1021/acs.inorgchem.7b02540
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly and Catalytic Reactivity of BINOL-Bridged Bis(phenanthroline) Metallocages

Abstract: Upon treatment with Zn ions, a series of BINOL-bridged bis(phenanthroline) ligands was self-assembled into [ML] metallocages, which were carefully characterized by NMR spectroscopy and ESI-MS spectrometry. Among them, a racemic mixture of the BINOL-bridged bis(phenanthrolines) underwent chiral self-sorting to afford two homochiral metallocages. The narcissistic self-sorting process of the metallocages was observed in the complexation reaction of the constitutionally isomeric bis(phenanthrolines) with varying c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…A control experiment without HAuCl 4 and CTAB showed that the organic part of nanospheres was still observed in the synthesis (Figure S4). Therefore, we strongly believe the nanospheres are BINOL-based molecular assemblies, owing to their intra/intermolecular interactions via π–π stacking and hydrogen bonding . Specific to the question to the reduction of HAuCl 4 , we postulate that the two hydroxyl groups of BINOL coordinate to the highly electrophilic Au­(III) centers, forming seven-membered ring organometallic Au complexes, previously reported .…”
Section: Results and Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…A control experiment without HAuCl 4 and CTAB showed that the organic part of nanospheres was still observed in the synthesis (Figure S4). Therefore, we strongly believe the nanospheres are BINOL-based molecular assemblies, owing to their intra/intermolecular interactions via π–π stacking and hydrogen bonding . Specific to the question to the reduction of HAuCl 4 , we postulate that the two hydroxyl groups of BINOL coordinate to the highly electrophilic Au­(III) centers, forming seven-membered ring organometallic Au complexes, previously reported .…”
Section: Results and Discussionmentioning
confidence: 74%
“…Therefore, we strongly believe the nanospheres are BINOLbased molecular assemblies, owing to their intra/intermolecular interactions via π−π stacking and hydrogen bonding. 22 Specific to the question to the reduction of HAuCl 4 , we postulate that the two hydroxyl groups of BINOL coordinate to the highly electrophilic Au(III) centers, forming sevenmembered ring organometallic Au complexes, previously reported. 23 Similar to the other phenolate complexes, the two consecutive O-anionic centers of binaphthol ligand are electron-rich, which render them effective reductants in the synthesis.…”
Section: ■ Results and Discussionmentioning
confidence: 80%
“…Among all other approaches, metal–ligand coordination-driven self-assembly has emerged as one of the best tools to construct two- and three-dimensional (2D and 3D) discrete architectures with predesigned size, shape, and functionality . Moreover, they have numerous synthetic benefits including high yield, one-pot easy synthesis, and kinetic reversibility leading to inherent self-correction of the final products . Different strategies such as the symmetry interaction model, face and edge directed self-assembly, and molecular library approach have been deployed to synthesize nanometer-size supramolecular coordination complexes (SCCs) .…”
Section: Introductionmentioning
confidence: 99%
“…Construction of supramolecular coordination complexes (SCCs) with well-defined nanosized cavities has attracted much attention, not only because of the fascinating structures but also the interesting host–guest chemistry and potential applications in catalyses, 1 supramolecular polymers, 2 photophysical properties, 3 separation, and recognition. 4 Coordination-driven self-assembly as a bottom-up approach has been proven to be an efficient method to assemble SCCs through carefully selecting building blocks.…”
Section: Introductionmentioning
confidence: 99%